2014
DOI: 10.1093/rheumatology/keu265
|View full text |Cite
|
Sign up to set email alerts
|

Long-term data on tacrolimus treatment in lupus nephritis

Abstract: The results suggest efficacy of TAC in LN, especially in reducing proteinuria, and its role as a long-term maintenance agent warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 23 publications
0
39
0
Order By: Relevance
“…Cyclophosphamide was reserved for patients with severe crescentic features in the kidney biopsy. Calcineurin inhibitors (CNI) were used as second-line treatment in patients who could not tolerate MMF, or as add-on therapy in patients who showed persistent significant proteinuria ( > 2g/D) despite standard therapy for 6 months [37]. Sirolimus was used in patients who could not tolerate standard immunosuppressants or who had a history of malignancy.…”
Section: Methodsmentioning
confidence: 99%
“…Cyclophosphamide was reserved for patients with severe crescentic features in the kidney biopsy. Calcineurin inhibitors (CNI) were used as second-line treatment in patients who could not tolerate MMF, or as add-on therapy in patients who showed persistent significant proteinuria ( > 2g/D) despite standard therapy for 6 months [37]. Sirolimus was used in patients who could not tolerate standard immunosuppressants or who had a history of malignancy.…”
Section: Methodsmentioning
confidence: 99%
“…Notwithstanding these limitations, it is generally agreed that patients with low levels of proteinuria, stable kidney function, low serological activity, no evidence or risk of concomitant severe proliferative features based on clinical judgment and an adequate renal biopsy should be managed with blood pressure control and renin-angiotensin pathway blockade, while patients with nephrotic and/or increasing proteinuria despite conservative management warrant an escalation of immunosuppressive therapy to aim for induction of proteinuria response [38,47]. The latter should be a combination of corticosteroids and any one of the following, CYC, AZA, MPA or a calcineurin inhibitor, and the efficacy of these treatment regimens has been observed in Asian patients [34,48,49,50]. …”
Section: Current Immunosuppressive Treatments For Ln: An Asian Perspementioning
confidence: 99%
“…Therefore, the safety of TAC, especially when given as long-term treatment, in patients with pre-established chronic kidney damage remains to be investigated. We have reported our data on the efficacy of TAC when used as add-on therapy, guided by therapeutic drug level monitoring, in patients with LN who showed persistent significant proteinuria despite treatment with other immunosuppressive agents, and in patients given long-term TAC therapy the renal survival rate at 3, 5 and 8 years was 93, 83 and 83%, respectively [50]. Mok et al [59] reported the outcomes of patients with class III/IV/V LN given corticosteroids and TAC as induction therapy followed by low-dose corticosteroids and AZA maintenance, and the complete remission rate at 6 months was comparable to that for patients treated with corticosteroids and MMF for induction followed by AZA during maintenance (59 vs. 62%; p = 0.71).…”
Section: Emerging Treatments In Asia and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Tacrolimus, a macrolide antibiotic that also inhibits calcineurin, was found to be more effective and safer than intravenous cyclophosphamide in induction treatment for Asians with proliferative or membranous lupus nephritis [25], [26]. Longterm tacrolimus treatment was also well tolerated and effective, especially in regards to reducing proteinuria, in a series of 29 Asian patients with lupus nephritis, but larger prospective studies including other racial groups are warranted [27]. A topical formulation of the calcineurin inhibitor pimecrolimus was comparable to betamethasone 0.1 % cream in a double-blind randomized controlled trial of facial discoid lupus [28].…”
Section: Surface and Intracellular Signaling In Sle T Cellsmentioning
confidence: 99%